Sowing dates and agronomic performance of soybean cultivars - Meotti, Giovane Vanin; Benin, Giovani; Silva, Raphael Rossi; Beche, Eduardo; Munaro, Lucas Berger (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of sowing dates on the agronomic performance of soybean cultivars in São Domingos, SC, Brazil, and to indicate stable and adapted cultivars for each sowing date. The experiment was carried out during two crop years (2008/2009 and 2009/2010), using six cultivars and four sowing dates (10/15, 11/15, 12/15, and 1/15), in a randomized complete block design, with three replicates and a usable plot area of 3.6 m2. The AMMI (additive main effects and multiplicative interaction analysis) method was used to evaluate the yield performance of the cultivars, and the GGE (genotype and genotype‑by‑environment) method to evaluate the adaptability and stability of the cultivars in each sowing date. In both crop years, the sowings on 10/15 and 11/15 maximized the number of pods per plant, the number of grains per pod, plant height, the number of branches, the weight of a thousand seeds, and, consequently, grain yield. Medium or early cycle cultivars, with high plant height, are more adequate for late sowing.